Visual computing technologies to support the Operator 4.0. (January 2020) - Segura, Álvaro; Diez, Helen V.; Barandiaran, Iñigo; Arbelaiz, Ander; Álvarez, Hugo; Simões, Bruno; Posada, Jorge; García-Alonso, Alejandro; Ugarte, Ramón
Highlights: Visual Computing technologies play a key role in empowering industrial operators. The Operator 4.0 concept is being implemented with support of Visual Computing. Examples of applications where operators are enhanced by technology are provided. Augmented reality, virtual reality, visual analytics support human operators. Abstract: Nowadays there is a clear trend for improving productivity and efficiency in the Industrial sector by integrating new advanced ICT technologies that are re-shaping the industrial production paradigms, as in the Industry 4.0 initiative. This new trend does not only affect production lines and machines but also operators. Markets demanding efficiency and flexibility would not be possible excluding the human-factor. Putting the operators in the centre of this new paradigm is mandatory for its success. The operators need to be empowered by giving them new tools and solutions for improving their decision-making processes. In this paper we show how Visual Computing technologies can play a key role in this empowering process, being therefore essential in the realization of the Operator 4.0 vision.